Discrete element modeling of realistic particle shapes in stone-based mixtures through MATLAB-based imaging process. (15th July 2017) - Liu, Yu; Zhou, Xiaodong; You, Zhanping; Yao, Shun; Gong, Fangyuan; Wang, Hainian
Highlights: Discrete element model with realistic particle shapes was newly developed for stone-based mixtures. Aggregate scanning approach was proposed for obtain particle images. A MATLAB-based imaging process was proposed to capture aggregate morphological features. A PFC5.0 Suite-based FISH codes was developed to re-built the geometry of stone-based mixture. Parametric analysis was performed and the computational efficiencies was discussed. Abstract: The objective of this paper is to present a newly-developed approach for discrete element simulation of realistic particle shapes in stone-based mixtures through a MATLAB-based imaging process and PFC5.0 Suite-based FISH codes to achieve both accuracy and efficiency. This newly-developed approach consists of three major steps, namely a MATLAB program for processing X-ray CT images of aggregates, a FISH code for generating discrete element models of individual aggregate particles, and a FISH code for creating the virtual sample of a stone-based mixture. In order to validate the newly-developed approach, parametric analysis was performed and the computational efficiencies of the ball-based model and the clump-based model were compared. It was found that both the MATLAB-based imaging processing method and the FISH codes of PFC5.0 were validated with high accuracy and efficiency.